(untitled) (Asian Journal of Pharmaceutics (AJP), 2022)
Background: The demand for a broad spectrum antimicrobial toothpaste is highly desirable to reduce, control, and prevent various types of dental diseases. Therefore, research into the production of herbal toothpaste to suppress the incidence of dental diseases is pertinent. Plant-based tooth paste has proved to be best at treating the gingivitis and other oral problems. Aim: In the present study, the herbomineral tooth paste was prepared using 18 different herbal ingredients which possess different uses both internally and externally and also four mineral salts that help to avoid tooth decay and gingival inflammation. The formulated toothpaste was evaluated for physicochemical properties and anti-bacterial activity. Methodology: Three different formulations were prepared and evaluated for various physicochemical properties such as stability, pH, homogeneity, compatibility with toothpaste packaging material, spreadability, abrasiveness, foaming ability, cleaning ability, and anti-bacterial activity that was tested on two bacteria, Staphylococcus aureus strain (MTCC 96) and Streptococcus mutans strain (MTCC 890) in comparison with commercial formulation, Vicco Vajradanth. Results: All the results of evaluated parameters showed that experimental formulation (F3) was comparably equal and better when compared with commercial formulation in terms of standards specified by the Bureau of Indian Standards 6356–1993 and found to be of good quality. The results were analyzed using two-way ANOVA. The results of the formulations are promising when compared to a commercial tooth paste. Conclusion: This formulation prevented the growth of S. mutans and S. aureus, organisms causing dental caries. This formulation maintains oral hygiene thereby preventing gingivitis and dental caries.